2017
DOI: 10.1186/s41476-017-0053-9
|View full text |Cite
|
Sign up to set email alerts
|

Research on edge-control methods in CNC polishing

Abstract: Background: We have developed edge-control for the Precessions TM process suitable for fast fabrication of large mirror segments, and other applications sensitive to edge mis-figure. This has been applied to processing of European extremely large telescope (E-ELT) prototype mirror-segments, meeting the specification on maximum edge mis-figure. However we have observed residuals that have proved impossible to correct with this approach, being in part the legacy of asymmetries in the input edge-profiles. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Based on the Preston equation, this analysis aims to predict the shape of the edge contour. Yu [17] showcased, through a simulation and experiments, that superior edge quality can be achieved by locally rectifying hexagonal optical lenses using small tools compared to machining large surfaces. Others have improved the edge effect by controlling the machining process.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Preston equation, this analysis aims to predict the shape of the edge contour. Yu [17] showcased, through a simulation and experiments, that superior edge quality can be achieved by locally rectifying hexagonal optical lenses using small tools compared to machining large surfaces. Others have improved the edge effect by controlling the machining process.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys such as that conducted by W. Song [11] have shown that the generalized spatial variable deconvolution algorithm can accurately calculate the dwell time, which can better control the actual removal amount so as to effectively suppress the edge error and improve the convergence rate. Based on the errors distribution on the workpiece, Yu et al [12] developed a new tool running path, which not only reduces residual errors on the edges but also the total polishing time.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method has better precision and robustness in scenarios of spectral aliasing or non-periodic apodization and potential applicability in various aspects of digital holography, interferometry, surface metrology, etc. [19][20][21][22]. This paper introduces the theory behind the method, analyzes the accuracy and adaptability with numerical simulations and experiment.…”
Section: Introductionmentioning
confidence: 99%